Transformasi Pembelajaran PAI Pasca Covid-19 di MIN 2 Aceh Tamiang - Savira, Izza Aulia; Utami, Sri; Lindawati (QuranicEdu: Journal of Islamic Education, 2025)
The Covid-19 pandemic had brought significant changes to various aspects of education, including Islamic Education (PAI) learning at MIN 2 Aceh Tamiang. This research aimed to analyze the transformation of PAI learning after the pandemic, including learning methods, curriculum/learning materials, and evaluation systems used to support the learning process. A qualitative descriptive research approach was used with data collection techniques through observation, interviews and documentation. The research results showed that MIN 2 Aceh Tamiang had made changes to learning methods, learning curriculum, and evaluation systems by adopting digital technology more widely, such as using online learning applications and social media as supporting tools. This transformation also encourages increasing teacher competence in integrating technology with PAI material. The findings of this research emphasized the importance of innovation and adaptation in post-pandemic learning to improve the quality of education.